2021
DOI: 10.1111/1467-9566.13272
|View full text |Cite
|
Sign up to set email alerts
|

The health effects of wage setting institutions: How collective bargaining improves health but not because it reduces inequality

Abstract: Do wage‐setting institutions, such as collective bargaining, improve health and, if so, is this because they reduce income inequality? Wage‐setting institutions are often assumed to improve health because they increase earnings and reduce inequality and yet, while individual‐level studies suggest higher earnings improve well being, the direct effects of these institutions on mortality remains unclear. This paper explores both the relationship between wage‐setting institutions and mortality rates whether income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…Our results are consistent with economic studies finding smoking is “inferior,” an economic term reflecting negative correlations between consumer products and income 29 . They are also consistent with Reeves' 4 finding of associations between higher unionization rates and lower mortality rates across 22 high-income countries that he attributes to the effects of unions on wages as well as O'Brien and colleagues' 30 finding that RTW predicted mortality across 50 states. Our results align with those from an IV study that finds higher wages reduce smoking prevalence among people with lower socioeconomic status 8 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with economic studies finding smoking is “inferior,” an economic term reflecting negative correlations between consumer products and income 29 . They are also consistent with Reeves' 4 finding of associations between higher unionization rates and lower mortality rates across 22 high-income countries that he attributes to the effects of unions on wages as well as O'Brien and colleagues' 30 finding that RTW predicted mortality across 50 states. Our results align with those from an IV study that finds higher wages reduce smoking prevalence among people with lower socioeconomic status 8 .…”
Section: Discussionsupporting
confidence: 90%
“…But laws are not the only way to raise wages; unions can too, as extensive economic research demonstrates. 2 Yet, we are aware of only two studies that even partially investigate the effects of union wage premiums on measures of health, 3,4 but one of these relies on ecological data, and neither uses causal models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Child mortality is an appropriate dependent variable because it is an important indicator of societal progress ( Sen, 1998 ), a key component of population health ( Reeves, 2021 ), and even a proxy for health inequalities, given that child mortality is often far higher among poorer households ( Baker et al, 2018 ). We use Ramos et al's long-run (more than 10 years) estimates of child mortality because the true impact of democratization on health takes time to emerge ( Gerring et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The share of the population that belongs to a union (union density) is associated with lower mortality in the population (Muntaner et al, 2002), better self-reported health (Dollard and Neser, 2013) and lower depression amongst the workforce, even for those who are not unionized (Reynolds and Buffel, 2020). Reeves (2021) shows that collective bargaining institutions reduce mortality and raise life expectancy at the country level. What is less well understood is for whom these beneficial effects apply.…”
Section: Dualization Collective Bargaining and Healthmentioning
confidence: 99%